Comparison between EUCAST Broth Microdilution and MIC Strip Test in Defining Isavuconazole In Vitro Susceptibility against Candida and Rare Yeast Clinical Isolates - Maddalena Calvo; Guido Scalia; Concetta Ilenia Palermo; Salvatore Oliveri; Laura Trovato (MDPI AG, 2023)
Isavuconazole is a new broad-spectrum triazole, with significant in vitro activity against yeasts. Isavuconazole in vitro susceptibility can be evaluated through broth microdilution as a reference method. Considering difficulties in equipping such methods in a laboratory routine, a commercial MIC Strip test has been designed. This study aims to implement data about isavuconazole in vitro activity and compare EUCAST broth microdilution and MIC Strip test in defining yeast isavuconazole susceptibility. The study involved 629 isolates from positive blood cultures (January 2017-December 2021). The identified species were C. albicans (283), C. glabrata (53), C. krusei (23), C. tropicalis (68), C. parapsilosis complex (151), C. guilliermondii (12), C. famata (6), S. cerevisiae (12), C. neoformans (5), S. capitata (12), and Rhodotorula species (4). All the isolates were tested with EUCAST microdilution and MIC Strip methods. The total essential agreement between these two methods was 99.3%. As a result, we can consider that both methods are useful in testing isavuconazole susceptibility. Proposed cut-off values (P-ECOFF) were calculated using ECOFFinder software. Further studies could lead to either definitive E-COFF or clinical breakpoints, which represent the most important categorization tool of the laboratory data, allowing a better insertion of an antimicrobial drug in clinical practice.